2000
DOI: 10.1093/jnci/92.14.1143
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of a Randomized Trial Comparing Breast-Conserving Therapy With Mastectomy: European Organization for Research and Treatment of Cancer 10801 Trial

Abstract: BCT and mastectomy demonstrate similar survival rates in a trial in which the great majority of the patients had stage II breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
550
2
23

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,136 publications
(604 citation statements)
references
References 19 publications
19
550
2
23
Order By: Relevance
“…Expected 5 year locoregional recurrence free, disease free and overall survival was also comparable between TNBC versus Non-TNBC patients. With a median follow up of more than four years, locoregional recurrence rate was comparable with randomized trials of BCT versus mastectomy (Van et al, 2000;Fischer et al, 2002).…”
Section: Discussionmentioning
confidence: 64%
“…Expected 5 year locoregional recurrence free, disease free and overall survival was also comparable between TNBC versus Non-TNBC patients. With a median follow up of more than four years, locoregional recurrence rate was comparable with randomized trials of BCT versus mastectomy (Van et al, 2000;Fischer et al, 2002).…”
Section: Discussionmentioning
confidence: 64%
“…Large prospective randomized trials have demonstrated that the survival rates after BCT are equivalent to those obtained after radical mastectomy [1][2][3]. The 5-year local-recurrence rate after BCT is about 5% with survival rates of approximately 92% [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…252 With this change came the increased use of RT as the preferred adjunctive approach in procedures that aim to conserve the breast. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Survival has increased with BCT and RT, and therefore the use of RT has grown exponentially. Long-term side effects of RT assume an increasingly important role in the development of SPMs.…”
Section: Original Research and Contributions Breast Cancer Survivorshipmentioning
confidence: 99%